High-strength core-shell silicon-carbon negative electrode material constructed based on multifunctional polymer additive and preparation method of high-strength core-shell silicon-carbon negative electrode material

By using multifunctional polymer additives to construct a three-dimensional core material in the preparation of silicon carbon negative electrode materials, and forming a high-strength core-shell structure through spray granulation and high-temperature coating processes, the problems of electrode structure failure and performance degradation caused by silicon expansion are solved, and the efficient preparation of the material and excellent electrochemical performance are achieved.

CN119852352APending Publication Date: 2025-04-18SICHUAN CHANGHONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895044.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing silicon-carbon anode materials have caused the electrode structure failure and performance degradation due to silicon expansion during electrochemical cycles. In addition, traditional preparation methods have problems such as expensive equipment, high energy consumption, large cost, long preparation cycles and uneven carbon coating.

Method used

Multifunctional polymer additives are used to assist in the construction of three-dimensional core materials, and through spray granulation and high-temperature coating processes, a high-strength core-shell silicon carbon negative electrode material is formed to ensure that the carbon layer is uniformly and closely covers the silicon particles, and enhances the conductivity and structural stability of the material.

Benefits of technology

It effectively solves the problems of electrode structure failure and performance degradation caused by silicon expansion, improves the cycle life and charge and discharge efficiency of the material, significantly reduces production costs and ensures consistency of product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005201513660000011
    Figure HDA0005201513660000011
  • Figure HDA0005201513660000012
    Figure HDA0005201513660000012
Patent Text Reader

Abstract

The invention discloses a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive and a preparation method of the high-strength core-shell silicon-carbon negative electrode material, and relates to the technical field of preparation of silicon-carbon negative electrode materials. The preparation method comprises the following steps: (1) in an inert atmosphere, putting a silicon source and a grinding aid into a grinding solvent, and grinding to obtain nano slurry; (2) carrying out spray granulation on the nano slurry, and calcining in an inert atmosphere to obtain a three-dimensional core material; and (3) uniformly mixing the three-dimensional core material and the carbon-coated material, coating at high temperature, crushing and screening to obtain the high-strength core-shell silicon-carbon negative electrode material constructed based on the multifunctional polymer additive. The three-dimensional core material is constructed under the assistance of the multifunctional polymer grinding aid, and the core material not only can improve the conductivity of the material, but also is beneficial to subsequent carbon coating, so that the high-strength core-shell silicon-carbon negative electrode material is formed, and the problems of electrode structure damage, performance reduction and the like caused by silicon expansion in the battery circulation process are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicon-carbon negative electrode material preparation, and in particular to a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive and a preparation method thereof. Background Art

[0002] As a negative electrode material for commercial lithium-ion batteries, graphite has good stability and conductivity, but its capacity is close to the limit and can only provide a specific energy of about 150 Wh / kg, which is difficult to meet the needs of electric vehicles for high-specific-energy batteries. Silicon has attracted much attention in recent years due to its high theoretical capacity and relatively low potential. However, during electrochemical cycles, silicon will produce a large volume expansion, resulting in loss of electrical contact and pulverization of silicon particles, resulting in poor cycle performance, rate performance and coulombic efficiency.

[0003] In the industry, silicon and carbon are often combined to prepare silicon-carbon negative electrode materials. The prepared composite materials have both high specific capacity and excellent cycle performance. In the preparation process of silicon-carbon negative electrode materials, common preparation methods include vapor deposition, sol-gel and sand milling. The vapor deposition method is mainly based on the chemical reaction between the gaseous silicon source and the carbon source under specific temperature, pressure and reaction atmosphere conditions, so that silicon and carbon atoms are deposited layer by layer on the substrate, thereby constructing a silicon-carbon composite structure; however, in the preparation method of the patented silicon-carbon negative electrode material and the silicon-carbon negative electrode and its application, this method relies on expensive equipment and complex vacuum systems, the preparation process has high energy consumption, high cost, slow reaction rate, and large-scale rapid production is difficult. The sol-gel method is to dissolve the silicon source and the carbon source in an appropriate solvent to form a uniform solution, and then gradually form a gel with a three-dimensional network structure through chemical reactions such as hydrolysis and polycondensation, and then obtain the silicon-carbon negative electrode material through subsequent processes such as drying and heat treatment; however, this method uses the sol-gel method to anchor ultrafine and high-purity SiO2 quantum dots on polydopamine nanospheres and prepare NC@Si composite materials through magnesium thermal reduction, but this method has a long preparation cycle, and is prone to cracking and agglomeration during the sol formation and gel drying process. The process conditions must be controlled very finely, and any slight error will cause large fluctuations in material performance. The sand milling method shows its unique advantages in the preparation of silicon-carbon negative electrode materials. This method can grind silicon to the required nanoscale particle size range more accurately. During the sand milling process, by setting specific sand milling parameters and adding appropriate grinding aids, the silicon particles can be evenly dispersed, effectively avoiding agglomeration. At the same time, combined with other process steps, a uniform and stable silicon-carbon composite structure can be prepared. At the same time, the sand milling method is more efficient and energy-saving than other preparation methods. Its equipment is easy to operate and maintain. It has strong application potential in large-scale industrial production of silicon-carbon negative electrode materials, which can effectively reduce production costs and ensure the consistency of product quality. For example, a patented method for preparing silicon-carbon negative electrode by sand milling combined with spray drying, in which the lithium source or magnesium source added to the slurry is decomposed at high temperature into lithium vapor or magnesium vapor and SiO2 on the silicon surface. x However, the sand grinding method of silicon-carbon negative electrode has some limitations. Under general preparation conditions, nano-sand grinding and carbon coating are difficult to carry out simultaneously. Since the two cannot be carried out at the same time, during the carbon coating process, it is difficult for the carbon source to be accurately and evenly deposited and coated on the surface of the sand-milled silicon particles, resulting in uneven thickness of the carbon coating layer and inability to form a tight and complete coating structure. This uneven coating condition leads to more gaps or weak bonding areas between carbon and silicon, and the tightness of the bonding between the two is greatly reduced. In the subsequent battery charge and discharge cycles, the volume expansion of silicon cannot be fully and effectively buffered and inhibited by the carbon layer, which can easily cause the shedding and structural damage of silicon particles, thereby having a negative impact on the overall electrochemical performance of the silicon-carbon negative electrode material, such as reducing the cycle life of the battery, affecting the charge and discharge efficiency, and causing increased capacity decay. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive and a preparation method thereof, with the help of a multifunctional polymer grinding additive to assist in constructing a three-dimensional core material. This core material can not only improve the conductivity of the material, but also facilitate subsequent carbon coating, thereby forming a high-strength core-shell silicon-carbon negative electrode material, which effectively solves the problems of electrode structure destruction and performance degradation caused by silicon expansion during battery cycling.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive is provided, comprising the following steps: (1) Under an inert atmosphere, place the silicon source and grinding aid in a grinding solvent and grind until the silicon source particle size D 50 ≤50 nm, nano slurry is obtained; (2) spraying and granulating the nano-slurry obtained in step (1), and then calcining it at 500-800° C. for 3-6 h under an inert atmosphere to obtain a three-dimensional core material; (3) The three-dimensional core material obtained in step (2) is evenly mixed with the carbon coating material, and high-temperature coating is performed at a temperature of 600-1200°C, crushed, and sieved to obtain a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive.

[0006] Furthermore, in step (1), the silicon source is one of polycrystalline silicon, single crystal silicon, metallic silicon, silicon alloy and silicon oxide.

[0007] Furthermore, in step (1), the grinding aid is at least one of carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, gum arabic, gelatin and guar gum.

[0008] Furthermore, in step (1), the grinding solvent is at least one of acetone, isopropanol, ethanol, n-hexane and N-methylpyrrolidone.

[0009] Furthermore, in step (1), the amount of grinding aid added is 0.1-10 wt % of the silicon source.

[0010] Furthermore, in step (2), micron-sized particles are formed after spray granulation.

[0011] Furthermore, in step (3), the amount of carbon coating material added is 20-60 wt % of the three-dimensional core material.

[0012] Furthermore, in step (3), the carbon coating material is at least one of graphite, asphalt, coke, acetylene black, petroleum coke, needle coke, lignin carbon, starch carbon, cellulose carbon, polyfurfuryl alcohol carbon and pyrolyzed polyacrylonitrile carbon.

[0013] Further, in step (3), the screening particle size D 50 8-25 μm.

[0014] The present invention also provides a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive, obtained by the preparation method of the high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive.

[0015] The present invention has the following beneficial effects: 1. The present invention adds a multifunctional polymer additive to the slurry. During the slurry grinding stage, the multifunctional polymer additive dissociates charged ions in the grinding solvent by virtue of specific functional groups on the molecular chain (such as the carboxymethyl functional group of carboxymethyl cellulose), charges the surface of the silicon particles, and uses the repulsion of like charges to prevent agglomeration, thereby ensuring that the silicon powder is evenly ground to a particle size D 50 ≤50 nm to obtain uniform nano-silicon slurry, and its good solubility and certain viscosity can stabilize the slurry system, which is beneficial to the subsequent process; during spray granulation, the multifunctional polymer additive interweaves and surrounds the nano-silicon particles, and forms a three-dimensional network structure through entanglement, adsorption, etc., which not only maintains the particle aggregation state to form micron-sized particles and ensures stability, but also provides an ideal template for orderly spatial distribution and connection for carbon coating, guiding the uniform deposition of carbon source; during the calcination process, the multifunctional polymer grinding aid is carbonized due to the interweaving distribution to form a special three-dimensional core material, which enhances the connection strength of silicon particles and provides solid support for carbon coating; in the carbon coating stage, the core structure formed by the carbonization of the multifunctional polymer grinding aid optimizes the surface state of silicon particles, so that the carbon source is tightly combined with the silicon particles and the carbonized multifunctional polymer grinding aid during high-temperature coating, forming a uniform and tight core-shell structure, and in the battery charge and discharge cycle, the carbon-silicon interaction is enhanced by virtue of its constructed structure, so that the carbon layer can effectively buffer the volume expansion of silicon, reduce the damage of the electrode structure and the degradation of material performance.

[0016] 2. In the process of preparing slurry by traditional sand milling, it is difficult to ensure that silicon particles are evenly and stably dispersed, and agglomeration is prone to occur, which is not only not conducive to the precise control of silicon powder particle size during sand milling, but also has a chain reaction of adverse effects on subsequent process steps. However, the present invention adds specific substances (such as carboxymethyl cellulose) to the slurry, and the functional groups (such as carboxymethyl) on its molecular chain can dissociate into charged ions in the grinding solvent, so that the surface of the silicon particles is charged. Based on the principle of like charges repel each other, the silicon particles can maintain a certain distance, which effectively prevents the agglomeration of particles in the slurry, ensures that the silicon powder can be evenly ground to the ideal particle size range, and lays a good foundation for the dispersion of silicon particles for the entire preparation process, greatly improving the stability and controllability of material preparation, which is an advantage that other sand milling methods cannot achieve.

[0017] 3. The traditional sand grinding method is difficult to carry out nano sand grinding and subsequent carbon coating simultaneously, making it difficult to accurately and evenly deposit and coat the carbon source on the surface of silicon particles, resulting in uneven thickness of the carbon coating layer. However, the present invention can provide good basic conditions for carbon coating through a unique process design (such as adding specific carboxymethyl cellulose to the slurry first), so that the carbon source can be evenly attached and extended along the constructed structure (such as the three-dimensional network structure formed by carboxymethyl cellulose), thereby achieving uniform and tight formation of the carbon coating layer on the surface of the silicon particles, effectively avoiding the problem of uneven coating in the traditional method.

[0018] 4. In the traditional sand grinding method, due to uneven carbon coating, there are many gaps or weak bonding areas between carbon and silicon, and the bonding is poor. The process constructed by the present invention can promote carbon and silicon to form a more tightly bonded structure, such as the high-strength core-shell silicon-carbon negative electrode material finally formed, in which the carbon layer is tightly connected to the silicon core, greatly enhancing the bonding force between the two, effectively making up for the defect of loose bonding in the traditional method.

[0019] 5. The materials prepared by the traditional sand grinding method cannot be fully buffered and inhibited by the carbon layer during the battery charge and discharge cycle because of the poor bonding between carbon and silicon, which easily causes silicon particles to fall off and structural damage. The silicon-carbon negative electrode material prepared by the present invention, with its uniform and tight carbon coating layer, can effectively restrain the excessive expansion of silicon with its excellent toughness and structural stability when silicon expands in volume during battery operation, significantly reducing the damage to the electrode structure caused by silicon expansion, and has outstanding performance in inhibiting silicon expansion, overcoming the shortcomings of traditional methods in this regard. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the three-dimensional core material obtained in Example 1; Figure 2 This is a SEM image of the high-strength core-shell silicon-carbon negative electrode material constructed based on the multifunctional polymer additive obtained in Example 1; Figure 3 This is a cycle performance diagram of the high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive obtained in Example 4. DETAILED DESCRIPTION

[0021] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0022] Example 1 A high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive, the preparation method of which comprises the following steps: (1) Under nitrogen atmosphere, place 100 g of silicon source (polycrystalline silicon) and 1 g of grinding aid (polyvinyl alcohol) in 1 L of grinding solvent (ethanol) and grind until the silicon source particle size D 50 ≤50 nm, nano slurry is obtained; (2) spraying and granulating the nano-slurry obtained in step (1) to form micron-sized particles, and then calcining them at 550° C. for 5 h under a nitrogen atmosphere to obtain a three-dimensional core material; (3) The three-dimensional core material obtained in step (2) was mixed evenly with 20 g of carbon coating material (petroleum coke), subjected to high-temperature coating at 850 °C, crushed, and sieved to obtain a particle size D 50 =10.3 μm, and a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive was obtained.

[0023] Example 2 A high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive, the preparation method of which comprises the following steps: (1) Under argon atmosphere, 100 g of silicon source (single crystal silicon) and 1 g of grinding aid (gum arabic) were placed in 1 L of grinding solvent (n-hexane) and ground until the silicon source particle size D 50 ≤50 nm, nano slurry is obtained; (2) spraying and granulating the nano-slurry obtained in step (1) to form micron-sized particles, and then calcining them at 650° C. for 3.5 h under an argon atmosphere to obtain a three-dimensional core material; (3) The three-dimensional core material obtained in step (2) was mixed evenly with 20 g of carbon coating material (cellulose carbon), and high-temperature coated at 950°C, crushed, and sieved to obtain a particle size D 50 =9.8 μm, and a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive was obtained.

[0024] Example 3 A high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive, the preparation method of which comprises the following steps: (1) Under helium atmosphere, place 100 g of silicon source (silicon alloy) and 1 g of grinding aid (gelatin) in 1 L of grinding solvent (acetone) and grind until the silicon source particle size D 50 ≤50 nm, nano slurry is obtained; (2) spraying and granulating the nano-slurry obtained in step (1) to form micron-sized particles, and then calcining them at 700° C. for 4.5 h in a helium atmosphere to obtain a three-dimensional core material; (3) The three-dimensional core material obtained in step (2) was mixed evenly with 20 g of carbon coating material (needle coke), subjected to high-temperature coating at 1050°C, crushed, and sieved to obtain a particle size D 50 =10.5 μm, and a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive was obtained.

[0025] Example 4 A high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive, the preparation method of which comprises the following steps: (1) Under nitrogen atmosphere, place 100 g of silicon source (silicon oxide) and 1 g of grinding aid (carboxymethyl cellulose) in 1 L of grinding solvent (N-methylpyrrolidone) and grind until the silicon source particle size D 50 ≤50 nm, nano slurry is obtained; (2) spraying and granulating the nano-slurry obtained in step (1) to form micron-sized particles, and then calcining them at 500° C. for 3 h under a nitrogen atmosphere to obtain a three-dimensional core material; (3) The three-dimensional core material obtained in step (2) was mixed evenly with 20 g of carbon coating material (asphalt), subjected to high-temperature coating at 1100 °C, crushed, and sieved to obtain a particle size D 50 =9.9 μm, and a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive was obtained.

[0026] Example 5 A high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive, the preparation method of which comprises the following steps: (1) Under argon atmosphere, place 100 g of silicon source (metallic silicon) and 1 g of grinding aid (sodium alginate) in 1 L of grinding solvent (isopropanol) and grind until the silicon source particle size D 50 ≤50 nm, nano slurry is obtained; (2) spraying and granulating the nano-slurry obtained in step (1) to form micron-sized particles, and then calcining them at 750° C. for 3 h under an argon atmosphere to obtain a three-dimensional core material; (3) The three-dimensional core material obtained in step (2) was mixed evenly with 20 g of carbon coating material (coke), and high-temperature coating was performed at 1150 °C, crushed, and sieved to obtain a particle size D 50 =10.2 μm, and a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive was obtained.

[0027] Comparative Example 1 A negative electrode material, the preparation method of which comprises the following steps: In a nitrogen atmosphere, 100 g of silicon oxide was selected as the silicon source, no grinding aid was added, and 1 L of N-methylpyrrolidone was used as the grinding solvent; the silicon powder was ground into a particle size of D 50 ≤50 nm, to obtain nano silicon slurry; spray granulation was carried out by spray drying process, and the particles obtained by spray granulation were placed in a muffle furnace in a nitrogen atmosphere and calcined at 500 ℃ for 3 hours, and then the material was mixed with 20 g of asphalt and coated at 1100 ℃, and finally crushed and sieved to obtain a silicon-carbon negative electrode material with a sieved particle size D50 of 9.9 μm.

[0028] Test example The SEM images of the three-dimensional core material obtained after calcination in Example 4 and the high-strength core-shell silicon-carbon negative electrode material constructed based on the multifunctional polymer additive are obtained, respectively. Figure 1-2 shown.

[0029] Depend on Figure 1 It can be seen that the three-dimensional core material prepared by the present invention presents a three-dimensional network structure, which can not only improve the conductivity of the material, but also serve as an attachment point for the subsequent carbon coating process to promote the carbon coating process.

[0030] Depend on Figure 2 It can be seen that the silicon-carbon negative electrode material obtained in the present invention has a uniform spherical structure, which is attributed to the internal three-dimensional core material, which creates favorable conditions for the attachment of carbon materials, greatly promotes the anchoring and uniform distribution of carbon materials on its surface, and together forms a high-strength core-shell silicon-carbon negative electrode material.

[0031] The negative electrode materials obtained in Examples 1-5 and Comparative Example 1 were subjected to electrochemical tests, and the results are shown in Table 1; and the high-strength core-shell silicon-carbon negative electrode material obtained in Example 4 was subjected to cycle performance tests, and the results are shown in Table 1. Figure 3 shown.

[0032] The electrochemical test process is as follows: CR2032 button cells were assembled using metallic lithium as the counter electrode, and the test conditions were: (a) Standing for 8 h; (b) 0.1 C rate discharge to 0.005 V; (c) Let stand for 1 min; (d) 0.1 C rate charging to 1.5 V; After the process step is completed, record the battery discharge capacity and first-cycle efficiency.

[0033] Table 1 Electrochemical test results of Examples 1-5 and Comparative Example 1 As can be seen from Table 1, the high-strength core-shell silicon-carbon negative electrode materials obtained in Examples 1-5 exhibit high capacity and first effect, in which the introduction of a multifunctional polymer grinding aid plays an extremely important role. The additive actively assists in the construction of a unique three-dimensional core material during the material preparation process, which not only makes up for the defect of poor conductivity of silicon, but also provides attachment points for the subsequent carbon coating process, significantly promoting the uniform coating of carbon, thereby obtaining a high-strength core-shell silicon-carbon negative electrode material. The high-strength core-shell silicon-carbon negative electrode material effectively inhibits the volume expansion of silicon during the cycle process and maintains the integrity of the electrode structure, thereby ensuring the excellent electrochemical performance of the battery. However, no additive was added to the blank group, the prepared material had poor conductivity, the carbon coating layer was loose and low in strength, silicon lacked effective constraints and buffering due to volume expansion, and the electrode structure was easily damaged, which led to rapid attenuation of the battery capacity and a significant reduction in the first effect. The overall electrochemical performance is far worse than that of the negative electrode material prepared in Examples 1-5 to which a multifunctional polymer grinding aid was added.

[0034] Depend on Figure 3 It can be seen that the high-strength core-shell silicon-carbon negative electrode material of the present invention exhibits extremely high capacity and high initial efficiency, the silicon charge and discharge platform is obvious, and the material exhibits good electrochemical performance.

[0035] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive, characterized in that: The following steps are involved: (1) In an inert atmosphere, place the silicon source and the grinding aid in a grinding solvent and grind until the silicon source particle size D 50 ≤50nm, nano slurry is obtained; (2) spraying and granulating the nano-slurry obtained in step (1), and then calcining it at 500-800° C. for 3-6 hours under an inert atmosphere to obtain a three-dimensional core material; (3) The three-dimensional core material obtained in step (2) is evenly mixed with the carbon coating material, and high-temperature coating is performed at a temperature of 600-1200° C., crushed, and sieved to obtain a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive.

2. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (1), the silicon source is one of polycrystalline silicon, single crystal silicon, metallic silicon, silicon alloy and silicon oxide.

3. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (1), the grinding aid is at least one of carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, gum arabic, gelatin and guar gum.

4. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (1), the grinding solvent is at least one of acetone, isopropanol, ethanol, n-hexane and N-methylpyrrolidone.

5. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (1), the grinding aid is added in an amount of 0.1-10 wt % of the silicon source.

6. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (2), micron-sized particles are formed after spray granulation.

7. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (3), the amount of the carbon coating material added is 20-60wt% of the three-dimensional core material.

8. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (3), the carbon coating material is at least one of graphite, asphalt, coke, acetylene black, petroleum coke, needle coke, lignin carbon, starch carbon, cellulose carbon, polyfurfuryl alcohol carbon and pyrolyzed polyacrylonitrile carbon.

9. The method for preparing a high-strength core-shell silicon-carbon negative electrode material based on a multifunctional polymer additive as claimed in claim 1, characterized in that: In step (3), the sieve particle size D 50 8-25μm.

10. A high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive, obtained by the preparation method of a high-strength core-shell silicon-carbon negative electrode material constructed based on a multifunctional polymer additive as described in any one of claims 1 to 9.